THE MECHANISM OF TRANSFORMATION OF THE LABOR MARKET OF UKRAINE TO THE NEW ECONOMY UNDER POST-CRISIS PERIOD - O. Komendant (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2013)
Major components of a mechanism of transformation of the Ukrainian labor market under new economy or knowledge-based economy are identified. Modern period of mechanism of transformation is considered. Level of implementation of the mechanism of transformation of the Ukrainian labor market under new economy is shown.